When income matters: Customers evaluation of shopping malls' hedonic and utilitarian orientations - ALLARD, Thomas (Institutional Knowledge at Singapore Management University, 2009)
This study, based on 772 shopper's interviews in two shopping malls, establishes that malls can achieve differentiation from their competitors through the pursuit of singular orientations following the hedonic and utilitarian dimensions of shopping. Furthermore, perceived differentiation from competitors is found to positively influence customers’ attachment to the mall, a determining factor in the mall's evaluation. Interestingly, mall's orientation related to hedonic elements was found appealing by all subjects, although slightly more by those with lower income. However, utilitarian orientation appeared strictly effective on those with higher income. Theoretical and managerial implications along with limitations are discussed.